2007
DOI: 10.1093/jn/137.4.1005
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Food Assistance Programs Modifies the Relation of Food Insecurity with Weight and Depression in Elders

Abstract: The relation of food insecurity in elders with outcomes such as overweight and depression, and the influence of participation in food assistance programs on these relations, has not been established. The aim of this study was to examine the relation between food insecurity and weight and depression in elders, and determine whether participation in food assistance programs modifies the effect of food insecurity on weight and depression. Two longitudinal data sets were used: the Health and Retirement Study (1996… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 60 publications
(80 reference statements)
10
106
0
4
Order By: Relevance
“…The current findings contribute additional evidence that health is adversely affected by an inability to meet essential needs for food, housing, and health care (10,(15)(16)(17). These findings are supported by others who report a positive relationship between material hardship and adverse health outcomes (15,17), financial hardship and depressive symptoms (10,11,23), and food insecurity and depressive symptoms among older adults (22). Several relevant studies have relied on longitudinal data for determining the relationship between material hardship or general financial hardship and depressive symptoms (10,22), which offer additional support for including the effects of hardship in studies of population health.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The current findings contribute additional evidence that health is adversely affected by an inability to meet essential needs for food, housing, and health care (10,(15)(16)(17). These findings are supported by others who report a positive relationship between material hardship and adverse health outcomes (15,17), financial hardship and depressive symptoms (10,11,23), and food insecurity and depressive symptoms among older adults (22). Several relevant studies have relied on longitudinal data for determining the relationship between material hardship or general financial hardship and depressive symptoms (10,22), which offer additional support for including the effects of hardship in studies of population health.…”
Section: Discussionsupporting
confidence: 77%
“…Estimates for the prevalence of depressive symptoms for homebound older adults vary from 28.8% (21) to 42% (11). Studies with older adults typically focus on the relationship between symptoms of depression and one component of material hardship such as food insecurity or general financial hardship (10,22,23). Unfortunately, no existing studies of older adults and depressive symptoms have placed financial hardship within the broader context of material hardship (10,11,16,23).…”
Section: Materials Hardship and Healthmentioning
confidence: 99%
“…Food insecurity in older adults is associated with numerous unfavorable nutrition and nonnutrition-related outcomes that may affect the health and well-being of the older population. Food insecurity is associated with low nutrient intakes (9,(28)(29)(30), increased nutrition risk (28,31), and unhealthy weight and body size (9,32). Food insecurity in older adults is also associated with poorer self-reported health status (9,23,28,33), anemia (23), multimorbidity and disability (30,34), poorer physical performance (23,33), lower cognitive function (35), anxiety and depression (23,32,36), and decreased quality of life (23,37).…”
Section: Determinants and Consequences Of Food Insecuritymentioning
confidence: 99%
“…13,14 Food insecurity, the limited availability of nutritionally adequate or safe food, or the inability to procure food in socially acceptable ways, 15 is an important form of socioeconomic marginalization. In the general population, food insecurity has been associated with many adverse health impacts, including poor nutritional status, [16][17][18][19][20][21] depression, [22][23][24][25][26] suicidal ideation, 26 obesity, 27 and increased cardiovascular risk. 28,29 Cross-sectional studies among non-HIV infected individuals in the US found that food insecurity is associated with postponing needed medications and care, increased emergency department use, and increased hospitalizations.…”
Section: Introductionmentioning
confidence: 99%